A GUI-based platform for quickly prototyping server-side IoT applications - Nepomuceno, Thiago; Carneiro, Tiago; Korn, Clemens; Martin, Alexander (Smart SysTech 2018 - European Conference on Smart Objects, Systems and Technologies, 2018)
This research work presents the AutoIoT, a platform conceived to generate server-side IoT applications. The AutoIoT platform provides a Graphical User Interface (GUI) to model an IoT system, and it applies a model-to-text transformation to generate a server-side application. The generated system is a complete Flask project, which follows the MVC pattern and is written in Python. Developers have full access to the source code of the generated system, which can be used as it is or extended to fulfil further requirements. The AutoIoT platform was used to model a real-world IoT scenario: an Assembly Line. According to the results, it is possible to conclude that AutoIoT is an effective tool for prototyping IoT systems.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Code Generation; Index Terms—Prototyping; IoT application; IoT platform; MDA